Mikroenkapsulasi Tiga Pewarna Alami dengan Konsep Warna Dasar Cyan, Magenta, Yellow (CMY) dari Ekstrak Bunga Telang, Kayu Secang, dan Kunyit - Musdalifa; Muthia Chairany; Nur Haliza; Februadi Bastian (Hasanuddin University Food Science and Technology Study Program, 2021)
Synthetic dyes in food can cause severe problems for health, so they need to be replaced by natural dyes. However, natural dyes are unstable, and encapsulation is one way to maintain the stability of natural dyes. This study was conducted to determine the best microencapsulation coating, storage stability, and color variations produced by butterfly pea, sappan wood, and turmeric extracts. The coating materials used were maltodextrin, carrageenan, and carboxy methyl cellulose (CMC) using the following formulations: 85% maltodextrin and 15% carrageenan (formula A) and 90% maltodextrin and 10% carrageenan (formula B) for coating butterfly pea and sappan wood extracts. Turmeric extracts were coating using 85% maltodextrin and 15% carrageenan (formula A) and 75% CMC and 25% starch (formula C). The encapsulation with maltodextrin (90%) and carrageenan (10%) was the best of encapsulation formula for butterfly pea and sappan wood extract. However, the encapsulation with maltodextrin (85%) and carrageenan (15%) was the best of encapsulation formula for turmeric extract. The green color was obtained from mixing butterfly pea and turmeric dyes in 1:4 ratio, purple from mixing butterfly pea and sappandyes in 1:8 ratio, and orange from mixing turmeric and sappan dyes in 1:2 ratio.